Contemporary strategic management approach in the defense system by U.S. methodology concept - Mrdak, Veselin I.; Petrović, Veljko P.; Luković, Branka R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The paper wants to emphasize the importance of contemporary strategic management approachs in the defense system. Displays the work of American author Leslie Lewis and C. Robert Roll "Strategy-to- tasks: a methodology for resource allocation and management". It were used by parts of the discussion above, in order to describe the strategy-to-tasks methodology for planning, programming and budgeting system (PPBS). In developed Western countries adopted some elements of strategic management to determine and monitor the execution of strategic plans in the defense system. This trend is spreading to other countries as a result of the necessity of obeying certain methodological and technological achievements. The uncritical acceptance of a strategic management approach can cause great confusion and problems, and the terminology and scientific explanation for this trend is of great importance. Introduction PPBS is a resource management framework based on force planning concept. It was developed at the lRand Company during the late eighties and is adapted to the special needs of several DoD organization. The planning, programming and budgeting system (PPBS) PPBS is DoD`ş primary system for planning and managing defense resources. It links the overall U.S. national security strategy to specific programs. It was designed to facilitate fiscally-constrained planning, programming and budgeting in terms of complete programs (i.e. forces and systems) rather than through artificial budget categories. The goal is to determine forces, systems and program costs. Strategy-to-tasks and the PPBS The Strategy-To-Tasks methodology, regardless of its application, it must be consistent and supportive of each phase of the PPBS. This section describes the basics frameworks of which are adapted to resource allocation and management activities for the Special Operations Command (USSOCOM). The authors have used it during the various phases of the PPBS. The National Security Strategy is formulated at the executive branch. National security objectives determine what must be done to preserve and protect the national principles, goals and interests in relation to the threats and challenges. National military objectives determine the manner in which national security strategy will be supported by the military. Operational objectives define the various military strategies. They describe how forces will be used to support the national military objectives. Tasks are accurately expressed by different levels of command (CINCs). They are the specific actions that must be performed in order to accomplish an operational objective. USSOCOMS and strategy-to-tasks The author concludes that any recommendation to USSOCOM for improving management and resource allocation had to contain the elements that DoD requires in various PPBS phase: links from the national security strategy down to specific military tasks. Moreover, these elements must be reliable, reproducible and easily verifiable. There were three proposals for improvement: 1. develop linkages between national securityobjectives and USSOCOM program resource needs, 2. change USSOCOM’s planning and programming processes, functions and data structures, 3. realign selected functions and organizational structure. USSOCOM and strategy-to-tasks framework Shows the revised Strategy-To-Taks framework as applied to USSOCOM. Force development issues in the U. S. Army Authors were asked to attempt to apply the STT methodology to facilitate development decision-making of U.S. military forces. The aim was on Army modernization. The approach that the authors outlined has enabled the U.S. Army to begin to evaluate its force structure and modernization programs against the other services by operational objective and task. The authors call this "competition among dissimilar systems." Institutionalize methodology Various application of mathodology are designed for STT simulation processes and connections among the commands and their associated elements. The authors point out that the application of the methodology STT shows how it can be developed and evaluated a complete operating concept. In this way, ensure that the logistical and other significant issues debated between the major military-related systems. The whole concept of an "operationalizing the PPBS process." Conclusion The main problems are observed using the approach of strategic management through literature and analysis of this example are: 1. proper determination of the strategic plan and its decomposition to lower down the strategic goals, objectives, processes, tasks and activities, 2. acceptance of the fact that the formulation and implementation of strategy is not a static process, 3. instead of a set of representative objectives the structure of objectives steers the organisation, 4. core structure of the objectives makes the process of harmonization of individual goals and their representation in the representative objectives, 5. implementation strategy consists in introducing the maximum number of persons with the basic hypotheses, 6. linking resources with hypotheses, a continuous test of the hypothesis and its application in real time. Every scientific theory has its own regularity of that time of origination, acceptance, implementation and application of the first serious critique of theory, important reductions, reshaping and creating new theories. The emergence and development of strategic management methodologies obvious example of the need and necessity of modern technology and the development of corporate culture and the Anglo-Saxon norm of civilization. Future direction of development strategic management methodologies is difficult to predict. The general impression is that the advent and advancement of strategic management methodologies that are organically connected with contemporary business information systems of this area substantially enclosed and that it has received the eventuaily contours.